Endothelial Dysfunction Driven by Hypoxia—The Influence of Oxygen Deficiency on NO Bioavailability - Janaszak-Jasiecka, Anna (Biomolecules, 2021)
Cardiovascular diseases (CVDs) are the leading cause of death worldwide. The initial stage of CVDs is characterized by endothelial dysfunction, defined as the limited bioavailability of nitric oxide (NO). Thus, any factors that interfere with the synthesis or metabolism of NO in endothelial cells are involved in CVD pathogenesis. It is well established that hypoxia is both the triggering factor as well as the accompanying factor in cardiovascular disease, and diminished tissue oxygen levels have been reported to influence endothelial NO bioavailability. In endothelial cells, NO is produced by endothelial nitric oxide synthase (eNOS) from L-Arg, with tetrahydrobiopterin (BH(4)) as an essential cofactor. Here, we discuss the mechanisms by which hypoxia affects NO bioavailability, including regulation of eNOS expression and activity. What is particularly important is the fact that hypoxia contributes to the depletion of cofactor BH(4) and deficiency of substrate L-Arg, and thus elicits eNOS uncoupling—a state in which the enzyme produces superoxide instead of NO. eNOS uncoupling and the resulting oxidative stress is the major driver of endothelial dysfunction and atherogenesis. Moreover, hypoxia induces impairment in mitochondrial respiration and endothelial cell activation; thus, oxidative stress and inflammation, along with the hypoxic response, contribute to the development of endothelial dysfunction.